Swedish national guidelines on urothelial carcinoma: 2024 update on advanced and metastatic disease - Anders Ullén; Firas Aljabery; Pär Dahlman; Karin Falkman; Truls Gårdmark; Tomas Jerlström; Susanna Holst; Sofia Kjellström; Anna-Karin Lind; Dimitrios Papantoniou; Jonas Stenlund; Viveka Ströck; et al. (Scandinavian Journal of Urology)
Objective: To overview and summarise the Swedish National Guidelines on Urothelial Carcinoma 2024.